Leukemia Inhibitory Factor: Roles in Embryo Implantation and in Nonhormonal Contraception - Naguib Salleh; Nelli Giribabu (The Scientific World Journal)
Leukaemia inhibitory factor (LIF) plays an indispensible role in embryo implantation. Aberrant LIF production is linked to implantation failure. LIF regulates multiple processes prior to and during implantation such as uterine transformation into a receptive state, decidualization, blastocyst growth and development, embryo-endometrial interaction, trophoblast invasion, and immune modulation. Due to its critical role, LIF has been a target for a nonhormonal contraception. In this review, we summarize up-to-date information on the role of LIF in implantation and its role in contraception.